Gamma Knife Treatment for Patients with Acoustic Neuroma: Bezmialem Vakif University Gamma Knife Unit Preliminary Results - HATİBOĞLU, MUSTAFA AZİZ; Hatiboglu, MUSTAFA AZİZ; OZGOR, Mahmut Hudai; DIK, Enes; SEYITHANOGLU, Hakan; TUZGEN, Saffet (My University, 2016)
Objective: Gamma knife is a stereotactic radiosurgical technique that focuses radiation on a specific target in the brain using 192 or 201 different Co60 sources. Because gamma knife is an effective and safe treatment, it is widely used for treating acoustic neuroma. In this study, patients with acoustic neuroma who were treated using gamma knife were reviewed, and the effectiveness and its side effects of the treatment were assessed. Methods: Patients with acoustic neuroma who underwent gamma knife between August 2014 and May 2015 were retrospectively reviewed. Magnetic resonance (MR) images of the brain before and after the treatment for every 3 months were assessed. In addition, during that period, clinical follow-up records were reviewed. Results: During the study period, 18 patients (11 males and seven females) were treated. Median age was 56 years (38-72 years). Lesion were present on the left side in 14 (78%), intracanalicular extensions in 15 (83%), and brainstem compressions in four (22%) patients were observed. The median tumor volume before gamma knife was 1.94 cm(3) (0.25-14 cm(3)). The median treatment dose was 12.5 Gy (12-13 Gy). Median follow-up duration was 4 months (1-8 months). Of the 18 patients, the lesion size decreased in three, increased in one, and remained stable in 14. Only one patient (% 6) developed hemiparesthesia, which resolved after steroid treatments. Conclusion: Gamma knife is an effective and safe treatment for treating patients with acoustic neuroma.
Keywords: Acoustic neuroma; Gamma knife; Stereotactic radiosurgery